Early economic evaluation of chelation therapy in kidney transplant recipients with high-normal lead - Jiasi Hao; Behrooz Z. Alizadeh; Maarten J. Postma; Daan J. Touw; Stephan J. L. Bakker; Lisa A. de Jong (PLoS ONE, 2025)
Background Kidney transplant recipients (KTR) with high-normal lead have a higher risk of graft failure (GF). Clinically, chelation therapy using meso-2,3-dimercaptosuccinic acid (DMSA) removes lead. Despite the proposal that chelation therapy can prevent GF through lead removal, evidence is lacking. To guide research efforts, we conducted an early economic evaluation, aiming to explore the economic feasibility of screening for and implementing chelation therapy with oral DMSA for high-normal plasma lead concentrations in KTR (i.e., the intervention) compared to standard of care. Methods A Markov model simulated the life course of 10,000 KTR in the Netherlands from a societal perspective. Transition probabilities were estimated using the data from TransplantLines Food and Nutrition Biobank and Cohort study. Costs and utilities were sourced from publications and public data. Model robustness was investigated through deterministic and probabilistic sensitivity analyses. Various administration strategies were tested. Five-year costs were calculated from a healthcare payer’s perspective. Value of information was assessed. Results The intervention was cost-saving and improved health, leading to a dominant incremental cost-effectiveness ratio. The result was most sensitive to transition probabilities (led by GF, followed by death with functioning graft and after graft failure). The probability of the intervention being cost-effective was 60%. Chelation strategies did not affect the result. The intervention applied to the Dutch KTR population could save €27 million in the initial five years. Further research is desirable if the cost of obtaining perfect information on GF survival is approximately below €4,000/KTR (all uncertainties under €5,000/KTR). Conclusion The cost-effectiveness of the intervention is robust in KTR, except when considering the uncertainties around (graft) survival probabilities. Applying chelation therapy in the new setting we studied holds significant potential. However, trials that systematically assess the efficacy, administration strategies, and impacts on survival are crucial in updating the current evaluation and informing policies.